A simplified new-generation renal mass complexity scoring system - Hajiran, Ali; Aydin, Ahmet M.; Cheriyan, Salim K.; Sexton, Wade J. (Annals of Translational Medicine; Vol 7, Supplement 6 (September 20, 2019): Annals of Translational Medicine, 2019)
Partial nephrectomy is the preferred surgical approach to localized renal tumors as this technique offers favorable oncologic outcomes and maximizes long-term renal function (1,2). Ten years ago, the first wave of standardized renal mass scoring nomograms was introduced to help clinicians objectively stratify the complexity of localized renal tumors and improve operative decision-making (3,4). Since that time, multiple series have validated the use of nomograms in predicting perioperative complications and outcomes following surgery and ablative procedures (5,6).